DOES EXCELLENT SERVICE MANAGEMENT IMPROVE ADMINISTRATIVE SERVICE QUALITY IN HIGHER EDUCATION? - Bagas Prakosa; Lisa Virdinarti Putra (El Midad, 2026)
Administrative service quality has become a critical component of student experience in higher education, particularly as institutions face increasing demands for efficiency, responsiveness, and service consistency. This study examines whether excellent service management significantly improves administrative service quality in higher education. Using a quantitative cross-sectional survey design, data were collected from 277 undergraduate students who had directly interacted with faculty-level administrative services. Excellent service management was operationalized through indicators of responsiveness, accuracy, timeliness, professionalism, clarity, and information consistency, while administrative service quality was measured using the SERVQUAL framework. Data were analyzed using descriptive statistics, validity and reliability testing, and simple linear regression analysis. The findings indicate that students generally perceive both excellent service management and administrative service quality positively. Regression results reveal a strong, significant effect of excellent service management on administrative service quality, accounting for 77.7% of the variance in students’ perceptions. Interpersonal service attributes emerged as the strongest, while digital responsiveness was identified as a key area for improvement. The study contributes to higher education service literature by empirically positioning excellent service management as a measurable antecedent of administrative service quality. Practically, the findings highlight the importance of aligning managerial service practices with both face-to-face and digital service delivery to support student-centered administration in higher education.